An analysis of the changing metaphors and concepts of mental health in psychoanalysis. - Oskowitz, Adina (My University, 2010)
There is a strong focus on defining and classifying psychopathology within a psychoanalytic paradigm. There is less emphasis on the consideration of what it means to be mentally healthy within a psychoanalytic framework. Yet, our understandings of mental health, whether implicit or explicit, inform our choices with our patients; our decisions to begin analytically oriented therapy, our treatment plans and our evaluations that termination has become appropriate. Therefore this research explores a fundamental underlying assumption that informs our work: what it signifies to be mentally healthy from a psychoanalytic perspective. In order to explicate understandings of mental health, the research explores the thought of four psychoanalytic theorists, Freud, Klein, Bion and Winnicott. The first part of the research examines the theories of the thinkers in order to extract their essential concepts and metaphors about mental health. For each thinker, a different emphasis on mental health is derived: Freud’s structural model is essential to his apprehension of mental health, for Klein the ability to experience affects and work through the depressive position is vital, for Bion the capacity to think and tolerate suffering is highlighted, while for Winnicott what becomes important is an individual’s capacity to inhabit transitional space. Next, these four approaches are discussed, compared and contrasted and the validity, or “mental health”, of each theory is considered. Finally, some contemporary approaches to mental health within psychoanalysis are explored. It is concluded that mental health in a psychoanalytic paradigm differs from psychiatric and other psychotherapeutic approaches to mental health. Mental health is not about cure, symptom elimination or efficient functioning in the world. Therefore, it is very important that psychoanalytically oriented therapists consider what it means to be mentally healthy within the terms of our discipline. While no one single definition is offered, it becomes clear that mental health is defined more in terms of one’s internal, psychic life as opposed to external functioning, is about tolerating process as opposed to fixating on end-goals and is concerned with a certain ongoing quality of relationship rather than the foreclosed elimination of a symptom.